Study of 21st-Century Skill Improvement for Prospective Biology Teacher Students Through the Lesson Study (LS) Model - Wikanta, Wiwi; Asy'ari, Asy'ari; Juniawan, Mulya Fitrah (Magister Pendidikan Biologi, Universitas Negeri Medan, 2023)
Education in Indonesia faces the problem of preparing human resources to face the world of work in the 21st Century Era. This study aims to describe the results of a Lesson Study on Improving 21st Century Skills for Biology Education Teacher Candidates at FKIP UMSurabaya. This research is a case study with a descriptive method. The research was conducted on the Department of Biology Education students for the 2019 Academic Year at FKIP UMSurabaya. Data were collected by documentation, test, and observation methods from 2 Lesson study cycles. Data were analyzed descriptively by calculating the percentage of students with HOTS, communication, and collaboration skill levels expressed in four categories. The results of the study showed: 1) the level of HOTS in the Very High Category in Cycles I and II was the same, namely 50% of students; 2) the level of Communication skills in the Very Competent Category in Cycle I was 26% of students and Cycle II was 36% of students; 3) the level of collaborative skills with the Very Competent Category in Cycle I was 25% of students, and Cycle II was 37% of students. The conclusion of this study shows that during Lesson Study, as many as two cycles of Biology Education Teacher Candidates at FKIP UMSurabaya have not shown an increase in HOTS. Meanwhile, his communication and collaboration skills have improved. The sustainability of the Lesson Study needs to be continued by building a learning community between lecturers of other subjects and partner teachers in schools.